Pelaksanaan Pengawasan Keselamatan Penerbangan di Bandar Udara SM. Badaruddin II Palembang - Lita Yarlina; Evy Lindasari (Research and Development Agency of The Ministry of Transportation, 2013)
Safety is a major factor every flight. National aviation safety oversight is one of the functions that are the responsibility of coaching the Derectorate General of Civil Aviation to encure compliance with the standards, procedures and regulations, in order to see the fulfillment of the terms and condition in general aviation safety standards and safe operation of airports in particular that carried out by the organizers airports and other stakeholders. The method of analisys used to determine the operational supervision airport is gap analysis between the observation and collection of primary data from airport managers with operational safety performance indicator airport contained in KM, 24 2009 on Civil Aviation Safety Regulation Part 139 on the airport (aerodrome) issued by the Directorate General of Civil Aviation. The analysis showed that the safety oversight of the airport operation in airport Sultan Mahmud Badaruddin II Palembang in the surveillance system consists of four systems which are airport management system, air side system control, the airport environment systems, inspection systems and reporting systems and safety management system has been appropriate and meets CASR 139.Pengawasan keselamatan penerbangan nasional merupakan salah satu fungsi pembinaan yang menjadi tanggung jawab Direktorat Jenderal Perhubungan Udara memastikan kesesuaian standar, prosedur dan peraturan terkait, guna melihat pemenuhan peraturan dan ketentuan standar dan keselamatan penerbangan pada umumnya dan keselamatan operasi bandar udara pada khususnya yang dilaksanakan oleh penyelenggara bandar udara dan pemangku kepentingan lainnya. Metode analisis yang digunakan untuk mengetahui pelaksanaan pengawasan operasional bandar udara adalah metode analisis kesenjangan (gap analysis)antara hasil observasi dan pengumpulan data primer dari pengelola bandar udara dengan performance indicator keselamatan operasional bandar udara yang terdapat dalam KM. 24 Tahun 2001 tentang Peraturan Keselamatan Penerbangan Sipil Bagian 139 (Civil Aviation Safety Regulation Part 139) tentang Bandar Udara (Aerodrome). Hasil analisis menunjukkan bahwa pengawasan keselamatan operasi Bandar udara di Bandar udara Sultan Mahmud Badaruddin II Palembang dalam sistem pengawasan terdiri dari 4 sistem yaitu sistem manajemen bandar udara, sistem control sisi udara, sistem lingkungan bandar udara, sistem pemeriksaan dan sistem pelaporan dan sistem Manajemen keselamatan sudah sesuai dan sudah memenuhi referensi CASR 139.